Wearable technologies for students with disabilities. Issue 4 (7th October 2021) - Conderman, Greg; Van Laarhoven, Toni; Johnson, Jesse; Liberty, Lisa
Abstract : Students with disabilities typically experience academic, social, and behavioural challenges in school. Some of these students also often experience anxiety and stress associated with school situations and events. Wearable technologies are an emerging innovation in the United States that can support students with disabilities during stressful academic or social situations. This article discusses issues associated with wearables, offers questions to consider when considering a wearable device for a student, and describes several wearable technologies for students with disabilities.